Sharing the load by one health: integrating canine rabies vaccination with bovine foot-and-mouth vaccination program and community public health services in rural Nilgiris District, Tamil Nadu, India - Ilona Airikkala-Otter; Julia Fröchlich; S Porkodi; Andrew Gibson; Luke Gamble; Emma Rayner (Wolters Kluwer Medknow Publications, 2022)
Background: India carries the largest national burden for rabies globally. Coordinating large-scale canine rabies elimination programs is challenging, particularly in rural areas, where the majority of human rabies deaths occur. This study evaluated the feasibility of combining canine rabies vaccination with pre-existing animal-health interventions or public health programs in a rural area of India. Materials and Methods: Canine rabies vaccination teams collaborated with a bi-annual bovine foot-and-mouth vaccination program coordinated by the Animal Husbandry Department (AH-collaboration) and with a village health program by the Public Health Department (PH-collaboration) in Nilgiris, Tamil Nadu, to vaccinate dogs during the implementation of these government-led health initiatives. Results: A total of 251 dogs were vaccinated over 7 days during the AH-collaboration, and 1083 dogs were vaccinated over 15 days during the PH-collaboration. The AH-collaboration achieved a vaccination coverage of 76% based on same-time sighting survey, and 58% based on post-vaccination survey. The PH-collaboration achieved vaccination coverage of 79% based on the same-time survey and 83% based on the post-vaccination survey. Conclusions: The integration of mass dog vaccination into existing government sector initiatives may facilitate the scaling up of canine rabies vaccination campaigns.